Монгол, хятад хэлний хүний бие эрхтний нэр бүхий хэлц үгийн тухай : On idioms of Mongolian and Chinese human body names - Л., Солонго (Mongolian Studies, 2023)
A wide range of Mongolian and Chinese language sayings incorporating the words for the human mouth (Mon. “am’’, Chin. “□ [kou]”) are used in everyday practice. In terms of their syntactic structure, Mongolian sayings are typically verbal whereas Chinese sayings typically involve a verb+object (动宾式); in terms of content they express meanings related to human activities, core qualities, and behaviour.